One‐Pot Green Process to Synthesize MXene with Controllable Surface Terminations using Molten Salts - Shen, Miao; Jiang, Weiyan; Liang, Kun; Zhao, Sufang; Tang, Rui; Zhang, Linjuan; Wang, Jian‐Qiang (Angewandte Chemie International Edition, 2021)
Surface terminations of two‐dimensional MXene (Ti3C2Tx) considerably impact its physicochemical properties. Commonly used etching methods usually introduce ‐F surface terminations or metallic impurities in MXene. We present a new molten‐salt‐assisted electrochemical etching method to synthesize fluorine‐free Ti3C2Cl2. Using electrons as reaction agents, cathode reduction and anode etching can be spatially isolated; thus, no metallics are present in the Ti3C2Cl2 product. The surface terminations can be in situ modified from −Cl to −O and/or −S, which considerably shortens the modification steps and enriches the variety of surface terminations. The obtained −O‐terminated Ti3C2Tx are excellent electrode materials for supercapacitors, exhibiting capacitances of 225 F g−1 at 1.0 Ag−1, good rate performance (91.1 % at 10 Ag−1), and excellent capacitance retention (100 % after 10000 charge/discharge cycles at 10 Ag−1), which is superior to multi‐layered Ti3C2Tx prepared by other etching methods. This is the first study to use a molten‐salt‐assisted electrochemical etching (MS‐E‐etching) method to synthesize Ti3C2Cl2 without metallic impurities. The Tx surface terminations could be in situ modified from −Cl to −O and/or −S in this one‐pot process. The obtained −O‐terminated Ti3C2Tx electrode exhibited a significant increase in capacity.